Revisiting lean healthcare: adopting value stream mapping from manufacturing - Alogla, Ageel (Frontiers in Health Services, 2025)
The application of lean thinking in healthcare has gained momentum in recent years, yet its implementation continues to face persistent challenges. Among these, staff resistance and conceptual misalignment between industrial principles and clinical environments remain significant barriers. This study argues that these issues stem not from the failure of lean theory itself, but from a flawed translation of lean tools, particularly Value Stream Mapping (VSM), from manufacturing to healthcare. To address this, we propose a systematic translation model that redefines key VSM elements (e.g., customer, inventory, takt time) in a way that aligns with the operational realities of outpatient care. The model is empirically validated through two case studies conducted in Saudi Arabia: an ophthalmology clinic and a dental clinic. By applying translated VSM tools, both clinics achieved substantial reductions in and patient waiting time, without compromising value-added care. The findings support the efficacy of contextualized lean implementation and provide healthcare managers with a practical framework for operational improvement. This study contributes to bridging the gap between lean theory and its real-world application in clinical settings.